Development of Shelf- Stable Pet Food Using Meat cum Bone Meal and Ghee Residue - C, Rani.; Govande, Prem Anand; T, Sathu. (Journal of Meat Science, 2011)
Shelf stable pet food (SSPF) was prepared by utilizing meat cum bone meal, refined wheat flour, blood serum, sugar, yeast, rendered fat (RF), and ghee residue (GR). Three formulations were prepared viz., 10% RF+0%GR (treatment-T1), 5%RF+5%GR (treatment-T2), and 0% RF+10% GR (treatment-T3) and analyzed for the proximate composition and acceptability test. The average moisture content of T1, T2 and T3 were 1.70%, 1.78% and 2.01% respectively and moisture of T3 was significantly (P<0.05) higher than T1, T2. Use of ghee residue significantly increased the protein content (from 26.83±0.16 to and reduced the fat content (from 14.37±0.17 to 9.92±0.12) in T2 and T3.. The calcium and phosphorus ratio of T1, T2 and T3 were 1.41, 1.62 and 1.67 respectively. Out of the three formulations T3 was more acceptable than T1 and T2.